If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(c + -1) + 69 = -3c Reorder the terms: 5(-1 + c) + 69 = -3c (-1 * 5 + c * 5) + 69 = -3c (-5 + 5c) + 69 = -3c Reorder the terms: -5 + 69 + 5c = -3c Combine like terms: -5 + 69 = 64 64 + 5c = -3c Solving 64 + 5c = -3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '3c' to each side of the equation. 64 + 5c + 3c = -3c + 3c Combine like terms: 5c + 3c = 8c 64 + 8c = -3c + 3c Combine like terms: -3c + 3c = 0 64 + 8c = 0 Add '-64' to each side of the equation. 64 + -64 + 8c = 0 + -64 Combine like terms: 64 + -64 = 0 0 + 8c = 0 + -64 8c = 0 + -64 Combine like terms: 0 + -64 = -64 8c = -64 Divide each side by '8'. c = -8 Simplifying c = -8
| 12(x+7)=4(x-1) | | 80+-2y=70 | | 4b^2-9b-34=0 | | U+4/5=-1/6 | | 0=6n-n^2 | | 30x-4=4(2x-0.3) | | -11x^2+1430x-4400=0 | | Y-7/8=-1/2 | | (x-10)+2y=70 | | 6(x-4)=-2x+24 | | 24(1/8y+37.5)+19y=1340 | | 6x+14=-7+x | | 4(x-1)=-3x+31 | | 9(3n-3)=(8n+4)+7 | | 14+6x=7-x | | 6g+7=-29 | | (2x+7)/8-2=x+(x-1)/2 | | 0=7(6-3x) | | 5.5(x-1)=0.5x+24.5 | | (t^2+7t-3)+(t^2+2t)= | | -0.3(2x-5)=0.7(6-x) | | x^3-9x^2-3x-27=0 | | 0.6x-3.6=0.6 | | (x/3)+x=(-10/9) | | x-1/6=-4/5 | | 0=-48+20p-2p^2 | | 62/20-27/10 | | 1600=16T^2 | | 3a+4=2+8 | | =1600 | | 5x^2+27x-98=0 | | 3(2x+7)=-27+6 |